Literacy opens up the universe - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
The Universe information centre of Akassato (BP 159, Ab-Calavi, Benin), reports its manager Jacques Sovi, is keen for contacts with other centres, and agencies which could assist in filling and organising its growing collection, which includes...